Who do They Tell? College Students' Formal and Informal Disclosure of Sexual Violence, Sexual Harassment, Stalking, and Dating Violence by Gender, Sexual Identity, and Race. Issue 21 (November 2022) - Mennicke, Annelise; Coates, Constance Austin; Jules, Bridget; Langhinrichsen-Rohling, Jennifer
Disclosure of interpersonal violence (i.e., sexual violence, sexual harassment, dating violence, and stalking) is often the first step toward receiving social and systemic support. Research demonstrates that sexual assault and dating violence survivors on college campuses are more likely to disclosure to informal sources (i.e., friends and family) than formal sources (e.g., police, Title IX, counseling centers). However, there is limited research examining disclosure rates after other forms of violence (i.e., stalking, sexual harassment), and little is known about the impact of the survivors' identities on disclosure. Utilizing four academic years (2016-2019) of aggregated campus climate data from a large Southeastern university, the current study examined rates of disclosure across experiences of sexual violence, sexual harassment, dating violence, and stalking while identifying whether the prevalence and type of disclosure (formal versus informal-only) differed by gender, sexual orientation, and/or race/ethnicity. Of 8, 017 participants, 4.6% reported sexual violence, 18.9% reported sexual harassment, 12.3% reported dating violence, and 11.3% reported stalking in the past academic year. Results of multinomial logistic regression indicated that, across all four types of violence, men (as compared to women) had lower odds of disclosing both informally-only and formally. Bisexual as compared to heterosexual students had higher odds of formal disclosure of sexual harassment and stalking while gay/lesbian students had higher odds of formally disclosing sexual harassment. Individuals of another race/ethnicity (compared to White students) had lower odds of informal-only disclosure of dating violence. Findings underscore the need to implement programs to improve the social reactions of friends and family members receiving disclosures, and to increase culturally-tailored service provision.